Farmers Extent of Adoption of Climate Resilient Agro-technologies: A Recent Study - Sobnam Sultana; Pabitra K. Das; Dipankar Saikia; Indrajit Barman (Modern Advances in Geography, Environment and Earth Sciences Vol. 4, 2021)
Climate change is possibly the most significant environmental challenge and possess serious threats to sustainable development in the world and more so in developing countries. Impact of climate change affects ecosystems, water resources, food and health. The most adverse effect of climate change is global warming. To adapt to the change and overcome the threats of climate change several climate-resilient agro-technologies have been introduced under the National Innovations on Climate Resilient Agriculture (NICRA) Project. The present study was conducted in Lakhimpur District of Assam to measure the extent of adoption of the climate-resilient agro-technologies introduced under the NICRA Project by the participant and non-participant farmers. A total of 160 farmers, 80 NICRA participant farmers and 80 non-participant farmers were interviewed. Findings revealed that the majority of the participant farmers (68.75 per cent) had a medium extent of adoption followed by 17.50 per cent with a low extent of adoption of climate-resilient agro-technologies. Only 13.75 per cent of the participant farmers were found to have a high level of adoption of climate-resilient agro-technologies. Among the non-participant farmers, majority of them (75.00 per cent) had a low extent of adoption followed by 17.50 per cent with a medium extent of adoption of climate-resilient agro-technologies. Only a very small proportion of them (7.50 per cent) had a high extent of adoption of climate-resilient agro-technologies. This implies that existing extension educational efforts made under the project need to be strengthened and streamlined to enhance the knowledge level of participant farmers on climate-resilient agro-technologies.